Prevalence and Identification of Some Ocular Bacterial Infections in Baghdad City - K. Khalil, Zena; K. Dewan, Eman; M. Ali, Thikra; S. Al-Kamil, Saif (Iraqi Journal of Science, 2021)
The study included 176 patients attended to Iben AL-Haithem hospital of ophthalmology in Baghdad city , at age of (14-77) years from the period from September 2016-April 2017, there were 138(78%) patients having a positive culture of ocular bacterial infections. Men were representing 41% while women 59%, the patients with bacterial ocular infection from Baghdad were55% while the internally displaced were 45% , the patients with ocular bacterial infections were representing 20% at mean age of 21.6±0.3y, 26% at 37.5±0.21y , 24% at53.5±0.23 y and 30% at69.5±0.10 y. The results showed 37% of the patients with ocular bacterial infections were having a history of diabetes mellitus and 44% with high blood pressure at mean age of 69.5±0.10 y. Gram positive bacteria represented 58% from the total isolates ,while gram negative were 42% . S.aureus was the common dominant isolates 29% followed by S.pneumoniae 21% , P.areuginosa 16% ,E coli 11% , Klibseilla spp 7% S.epidermidis 6%,Enterobacter spp6% , S.pyogenes 2% , Citrobacter freundii and Proteus spp 1% each of them , the mix infection was found in three samples including (E. coli and P. aeruginosa),( E. coli and S. aureus) and (P. aeruginosa and S. aureus) . S. aureus isolates were susceptible to Amikacin 88%, Doxycycline 84% and they were highly resistance to Clindamycin 76% , while S.epidermidis isolates were susceptible to each of Amikacin, Cloramphenicol , Clindamycin and Doxycycline at a percentage of 80% and they were resistance to tetracycline 60% . S.pneumoniae isolates were susceptible to Clarithromycin 94% , Ceftriaxone 88%, S.pyogenes isolates were susceptible 100% to the most types of antibiotics such as Erythromycin , Clarithromycin , Cloramphenicol , Clindamycin and Ceftriaxone . P.areuginosa isolates were susceptible to Gentamicin 100%.,Ciprofloxacin , Doxycycline , Amikacin 72% for each antibiotic ,while E.coli isolates were susceptible to Cloramphenicol 90%, Ciprofloxacin and Gentamicin 80%. Klibseilla spp isolates were susceptible to Ciprofloxacin and Gentamicin 100%, Ceftriaxone 83% while Proteus spp isolate were susceptible to all types of antibiotics 100% Enterobacter spp isolates were susceptible to Ciprofloxacin 100% ,both of Gentamicin and Cloramphenicol 80% , Citrobacter freundii isolate were susceptible to Ceftriaxone , Cloramphenicol , Ciprofloxacin , Gentamicin 100%.